PREPARASI EKSTRAK BAYAM MERAH (AMARANTHUS GANGETICUS) UNTUK APLIKASI DYE SENSITIZED SOLAR CELL (DSSC) - Farradina Choria Suci; Arnisa Stefanie (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Solar energy is the most beneficial renewable energy, because it is not limited, not called by geographical location, and not environmental pollution. Solar energy can be converted into electrical energy using Solar Cells. Dye Sensitized Solar Cell (DSSC) is a form of renewable energy with several advantages, such as low fabrication costs and high photoelectric efficiency. The structure of the DSSC device consists of five components, namely conductive substrate, semiconductor filmization, sensors, redox in the form of electrolytes and opposing electrodes. The proper use of semiconductor materials and photosensitizers can produce high photoelectric power. Included in the DSSC application, dyestuff is a component that has an important role. In this study, dye extraction was done using red spinach leaves (Amaranthus gangeticus) with maceration techniques. Red spinach is one potential that can be developed into dyes because the red color of spinach contains natural pigments. Red spinach extract uses maceration techniques because of simple and sophisticated workmanship that is simple. The results of the red spinach extract were then tested using UV-Vis, FTIR, and cyclic voltammetry.